2000
DOI: 10.1161/01.cir.101.25.2909
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Principle of Signal-Averaged Electrocardiography

Abstract: Within the acceptable noise range for SAECG, lower noise results in longer QRSd and larger variance, suggesting that more accurate recordings may have less reproducibility. The random timing of noise relative to signal results in the distribution/variance of repeated measurements. Statistical strategies may be used to reduce some of this variance and may enhance the diagnostic utility of SAECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…On the other hand, the morphology and the location of VLPs, as well as the parameters employed in signal acquisition and processing, even when standardized (Breithard et al, 1991), influence the precision and the accuracy of QRS complex end points (QRS offset) estimation. A residual variability in QRS duration in successively performed exams is, thus, observed in the same patient (Goldberger et al, 2000). Notwithstanding, the duration of the QRS complex is the most important index for the risk stratification of ventricular arrhythmia (Uijen et al, 1979;Korhonen et al, 2006;Marcus et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…On the other hand, the morphology and the location of VLPs, as well as the parameters employed in signal acquisition and processing, even when standardized (Breithard et al, 1991), influence the precision and the accuracy of QRS complex end points (QRS offset) estimation. A residual variability in QRS duration in successively performed exams is, thus, observed in the same patient (Goldberger et al, 2000). Notwithstanding, the duration of the QRS complex is the most important index for the risk stratification of ventricular arrhythmia (Uijen et al, 1979;Korhonen et al, 2006;Marcus et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
“…The classic theory, proposed by Uijen et al (1979) establishes that the variability of any point along the QRS complex, identified by a threshold detector level, will be directly proportional to RNL and inversely proportional to the first derivative at the detection point. On its turn, the uncertainty principle applied to HRECG (Goldberger et al, 2000) states that the lower RNL, the higher the variability (uncertainty) in the estimated QRS offset in successive independently processed HRECG signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the upper part of fig. 5 we have plotted to series describing the fluctuations of walk rhythm of a young healthy person, for slow pace (bottom series of 3304 points) and fast pace (up series of 3595 points) respectively (data available in www.physionet.org/physiobank/database/umwdb/ (Goldberger et al, 2000)). In the bottom part we have represented the degree distribution of their visibility graphs.…”
Section: Estimating the Hurst Exponent With Nvgmentioning
confidence: 99%
“…The authors proposed the validation of the BiSpec, but did not perform clinical comparisons of the diagnostic results of the two filters using control groups. Recently, Goldberger et al (10) reported that paired differences of filtered QRS duration between the BiSpec and Butterworth bidirectional filters were not statistically significant, although there was a high variance of paired difference of the filters' output at 61.1 ms (2).…”
Section: Introductionmentioning
confidence: 99%